Magnetic Dextran Nanoparticles That Bear Hydrophilic Porphyrin Derivatives: Bimodal Agents for Potential Application in Photodynamic Therapy. Issue 9 (26th August 2015) - Mbakidi, Jean‐Pierre; Brégier, Frédérique; Ouk, Tan‐Sothea; Granet, Robert; Alves, Sandra; Rivière, Eric; Chevreux, Sylviane; Lemercier, Gilles; Sol, Vincent
Abstract Invited for this month's cover is the group of Prof. Vincent Sol from the University of Limoges, France. This study is a collaboration between the Universities of Limoges, Reims, Pierre et Marie Curie (UPMC, Paris), and Paris Sud (Orsay). The cover picture shows a magnetic dextran nanoparticle bearing hydrophilic porphyrin derivatives; the illustration shows bimodal nanoplatforms that could be used as contrast agents in magnetic resonance imaging as well as photosensitizers in photodynamic therapy. Read the full text of the article at 10.1002/cplu.201500087.